2016
DOI: 10.1007/s00380-016-0896-9
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 1-year clinical outcomes using the SYNTAX score in patients with prior heart failure undergoing percutaneous coronary intervention: sub-analysis of the SHINANO registry

Abstract: Although coronary artery disease (CAD) is common in patients with heart failure (HF), little is known about the prognostic significance of coronary lesion complexity in patients with prior HF undergoing percutaneous coronary intervention (PCI). The aim of this study was to investigate whether the coronary Synergy between Percutaneous Coronary Intervention with TAXus and Cardiac Surgery (SYNTAX) score could improve risk stratification in HF patients with CAD. Two hundred patients (mean age 73 ± 11 years, left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…SS is usually used for calculating the severity and complexity of CAD and as a guideline for interventional cardiologist to choose more appropriate treatment between percutaneous coronary intervention (PCI) and coronary artery bypass graft surgery [21]. There is increasing evidence that has proven that this scoring system could predict major adverse cardiovascular events in patients with ACS or undergoing PCI [22, 23]. As in line with previous studies, in the present study, patients with higher SS have higher in-hospital mortality rate than patients with lower SS [7].…”
Section: Discussionmentioning
confidence: 99%
“…SS is usually used for calculating the severity and complexity of CAD and as a guideline for interventional cardiologist to choose more appropriate treatment between percutaneous coronary intervention (PCI) and coronary artery bypass graft surgery [21]. There is increasing evidence that has proven that this scoring system could predict major adverse cardiovascular events in patients with ACS or undergoing PCI [22, 23]. As in line with previous studies, in the present study, patients with higher SS have higher in-hospital mortality rate than patients with lower SS [7].…”
Section: Discussionmentioning
confidence: 99%
“…New scientific reports have shown that this scoring system is also capable of predicting major cardiovascular events in patients undergoing PCI. [2] In other words, patients with a high SYNTAX score had lesions that were more complicated and resulted in worst prognosis following PCI.…”
Section: Introductionmentioning
confidence: 99%
“…To further support this analysis, the SHINANO registry showed SYNTAX score to be beneficial in predicting the incidence of MACEs following PCI 20 . That particular registry included patients with prior heart failure and coronary artery disease.…”
Section: Discussionmentioning
confidence: 95%